Internalization Of Islamic Education Through The Activities Of Pentas PAI (Inovasi: Jurnal Diklat Keagamaan, 2021)
This article presents the results of research on the development of religious education in elementary schools in order to internalize religious values ​​in students at SDN 1 Pengadilan Tasikmalaya City. This research is motivated by the opinion that learning PAI is only focused on aspects of knowledge or cognitive. While the affective and psychomotor aspects are ignored. Teachers are only focused on achieving school curriculum content. This research is a descriptive qualitative research. Data were collected by interview, observation and documentation study. The results of this study produce several conclusions as follows: First through the activities of the PAI stage as a religious activity the process of interalisation of religious values ​​is easy to apply. Second, through learning outside the classroom through the PAI stage will make PAI learning more enjoyable. Third, PAI learning by combining learning activities in class with extracurricular activities will produce a more varied learning model. Fourth, the stage of PAI as a religious activity in the form of Islamic arts and culture becomes an alternative planting of religious values ​​that is more easily accepted by students because it is more pleasing.
Keywords: PAI Performance, Internalization, PAI, Activities